Knockdown of lncRNA LEF1-AS1 inhibited the progression of oral squamous cell carcinoma (OSCC) via Hippo signaling pathway. Issue 9 (2nd September 2019) - Zhang, Chanqiong; Bao, Chunchun; Zhang, Xiuxing; Lin, Xinshi; Pan, Dan; Chen, Yangzong
ABSTRACT: It is verified that long non-coding RNAs (lncRNAs) play crucial roles in various cancers. LncRNA LEF1-AS1 is a reported oncogene in colorectal cancer and glioblastoma. In this study, we unveiled that LEF1-AS1 markedly increased in oral squamous cell carcinoma (OSCC) tissues and cell lines. Besides, OSCC patients with high levels of LEF1-AS1 were apt to poor prognosis. Functionally, LEF1-AS1 knockdown inhibited cell survival, proliferation and migration, whereas enhanced cell apoptosis and induced G0/G1 cell cycle arrest in vitro. Consistently, LEF1-AS1 silence hindered tumor growth in vivo. Moreover, LEF1-AS1 inhibition stimulated the activation of Hippo signaling pathway through directly interacting with LATS1. Furtherly, we disclosed that LEF1-AS1 silence abolished the interaction of LEF1-AS1 with LATS1 while enhanced the binding of LATS1 to MOB, therefore promoting YAP phosphorylation but impairing YAP1 nuclear translocation. Additionally, we demonstrated that LEF1-AS1 regulated YAP1 translocation via a LATS1-dependent manner. Furthermore, we also uncovered that YAP1 overexpression abolished the suppressive impact of LEF1-AS1 repression on the biological processes of OSCC cells. In a word, we concluded that LEF1-AS1 served an oncogenic part in OSCC through suppressing Hippo signaling pathway by interacting with LATS1, suggesting the therapeutic and prognostic potential of LEF1-AS1 in OSCC.